Technical Feasibility and Constraints of Pen Aquaculture in Floodplain Wetlands (Beels) Of Assam, India - Alakesh Dasa; Paramita Banerjee Sawant; B. K. Bhattachariya; N. K. Chadha; A. K. Verma; S. N. Goswami; D. Debnath; S. Vengkokpam; A. Kakati; P. Das; A. K. Vadav (Journal of Indian Fisheries Association, 2018)
Technical feasibility and constraints of pen aquaculture technology in floodplain wetlands (beels] of Assam, India were assessed based on data from 22 pens (0.25 ha each) in 22 wetlands in ten districts of Assam for rearing carp fingerlings. Personal interviews and focussed group discussions with respondents yielded eight technical feasibility criteria for Rank-based Quotient (RBO) analysis. 'Ease of operation', 'easy availability of bamboo for pen construction', 'weaving traditional split-bamboo screens (banal' and 'availability of unskilled labour for pen construction at wetland sites' were chronologically important among technical feasibility criteria. Constraint analysis for pen aquaculture through preferential ranking technique delineated as many as twelve constraints with RBQ values. Major constraints in effective dissemination and adoption of pen aquaculture technology wore "poaching and poisoning, increasing cost of inputs (lish seed, feed, etc), lesser growth of hatchery-raised seed, increasing cost of bamboo and labour' and "Inadequate technical know-how and awareness. The study suggests that facilitating larger scale adoption of the technology following a cluster approach would not only reduce poaching and poisoning but would also make essential inputs (fish seed, fish feeds, etc) available at all regions of Assam to popularize pen aquaculture to enhance productivity of wetlands and livelihood of wetland fishers.